Physical and sports activities of students with intellectual disabilities - Golikova, Elena M. (Физическое воспитание и студенческий спорт)
The relevance of the article is conditioned by the necessity to transform physical and sports activities in the system of education for students with intellectual disabilities. Priority directions in developing education for students with intellectual disabilities for the long-term period are designed to determine a set of priority measures and the sequence of their implementation. More precisely, it is necessary to ensure availability of educational practices (correctivedevelopmental, adaptive- sports and leisure activities) through the implementation of inclusive and adapted programs of extracurricular physical and sports activities, justified by the need of psychophysical development of this category of students. The aim of the study is to identify accessible physical and sports activities for students with intellectual disabilities in secondary vocational education. The author reveals the main directions of physical education and sports activities of students with intellectual disabilities, offers an individual educational trajectory in the construction of extracurricular health and sports activities, aimed at health-improving, socializing, and corrective outcomes. High motivation for motor activity and interest in adaptive sports (Ucr – 62) are the result of involving students with intellectual disabilities in extracurricular physical and sports activities. The health-improving result is reflected in significant changes in the functional state of the cardiorespiratory system (Ucr – 87) and the development of a healthy lifestyle (Ucr – 8). The results of physical fitness when performing test tasks has increased (Ucr – 29.5). There are positive changes in the tests “volitional self-regulation” (Ucr – 87) and “goal achievement” (Ucr – 75.5). During the classes, there was activity, interaction between students with intellectual disabilities and students with no deviations in the state of health.